Stylosanthes as a forage and fallow crop. Proceedings of a regional workshop on the use of Stylosanthes in West Africa - Leeuw, P.N. de; Mohamed-Saleem, M.A.; Nyamu, A.M. (International Livestock Centre for Africa, 1994)
This report is divided into seven sections. The first section deals with biology of Stylosanthes and its importance in West Africa and Latin America. The second section presents papers on the screening and evaluation of Stylosanthes germplasm. This includes genetic diversity, genetic resources, species screening, multi-locational testing and evaluation of accessions. The third part discusses the dynamics, nutrient requirements, and pests and diseases of Stylosanthes species. Section four looks at Stylosanthes-based pastures for livestock production. This section examines stylo-based pasture development, stylo as a source of supplementary feeding, development of grazing, crop-livestock farming system, and evaluation of stylo-grass mixtures. The fifth section examines the integration of Stylosanthes into cropping systems. Some of the topics covered under this topic are establishment techniques, development of millet-stylo cropping systems and research approach and methodologies. The sixth section is on seed production of Stylosanthes and the last section discusses the impact of Stylosanthes.